Apatinib Induces Ferroptosis of Glioma Cells through Modulation of the VEGFR2/Nrf2 Pathway. (11th May 2022) - Xia, Liang; Gong, Mingjie; Zou, Yangfan; Wang, Zeng; Wu, Bin; Zhang, Shuyuan; Li, Liwen; Jin, Kai; Sun, Caixing
Abstract : Background . Glioma is a common tumor that originated from the brain, and molecular targeted therapy is one of the important treatment modalities of glioma. Apatinib is a small-molecule tyrosine kinase inhibitor, which is widely used for the treatment of glioma. However, the underlying molecular mechanism has remained elusive. Recently, emerging evidence has proved the remarkable anticancer effects of ferroptosis. In this study, a new ferroptosis-related mechanism of apatinib inhibiting proliferation of glioma cells was investigated, which facilitated further study on inhibitory effects of apatinib on cancer cells. Methods . Human glioma U251 and U87 cell lines and normal astrocytes were treated with apatinib. Ferroptosis, cell cycle, apoptosis, and proliferation were determined. A nude mouse xenograft model was constructed, and tumor growth rate was detected. Tumor tissues were collected to estimate ferroptosis levels and to identify the relevant pathways after treatment with apatinib. Results . Treatment with apatinib could induce loss of cell viability of glioma cells, but not of normal astrocytes, through eliciting ferroptosis in vitro and in vivo. It was also revealed that apatinib triggered ferroptosis of glioma cells via inhibiting the activation of nuclear factor erythroid 2-related factor 2/vascular endothelial growth factor receptor 2 (Nrf2/VEFGR2) pathway. The overexpression of Nrf2 rescued the therapeutic effects of apatinib. Conclusion . Our study proved that treatment with apatinib could restrain proliferation of glioma cells through induction of ferroptosis via inhibiting the activation of VEGFR2/Nrf2/Keap1 pathway. Overexpression of Nrf2 could counteract the induction of ferroptosis by apatinib.